2022
DOI: 10.1186/s12882-022-02693-y
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and iron for anemia in HIV-infected patients undergoing maintenance hemodialysis in China: a cross-sectional study

Abstract: Background Anemia is a common complication of chronic kidney disease (CKD) and HIV infection. The number of people living with HIV on hemodialysis (HD) is increasing. However, there is no data about anemia and related therapies in this kind of patients in China. We aim to assess the difference in hemoglobin (Hgb) and treatments like erythropoietin and iron between HIV-HD patients and HD patients in Chengdu, China. Methods This cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…CKD and chronic anemia in this population are associated with adverse outcomes, including increased morbidity and mortality, and are linked to cardiovascular disease (CVD) [ 111 ]. Anemia is a common complication in both CKD and HIV infection, associated with an elevated risk of cardiovascular events and all-cause mortality [ 112 ]. In CKD, anemia, linked to reduced erythropoietin production, contributes to cardiovascular risk by promoting markers of endothelial activation and left ventricular hypertrophy [ 113 ].…”
Section: Chronic Anemia In Hiv Is Associated With Chronic Kidney Dise...mentioning
confidence: 99%
See 1 more Smart Citation
“…CKD and chronic anemia in this population are associated with adverse outcomes, including increased morbidity and mortality, and are linked to cardiovascular disease (CVD) [ 111 ]. Anemia is a common complication in both CKD and HIV infection, associated with an elevated risk of cardiovascular events and all-cause mortality [ 112 ]. In CKD, anemia, linked to reduced erythropoietin production, contributes to cardiovascular risk by promoting markers of endothelial activation and left ventricular hypertrophy [ 113 ].…”
Section: Chronic Anemia In Hiv Is Associated With Chronic Kidney Dise...mentioning
confidence: 99%
“…The study by Li et al (2022) utilized humanized mice as a robust animal model to investigate the impact of chronic HIV-1 infection on HPCs [45]. The investigators found that HIV-1 infection significantly depleted the population of CD34+CD38-early HPCs in the bone marrow of humanized mice.…”
Section: Hiv Reactivation and Infection Of Hematopoietic Stem Cells M...mentioning
confidence: 99%